Oficina Avni - Studio Avni, Studio Avni (Base Diseño e Innovación, 2015)
Studio Avni is a multidisciplinary design studio offering bespoke 3D textiles, furniture, lights and products using unconventional materials. Headed by Architect and Designer Avni, the studio explores a wide spectrum of design innovations through research and tactile manipulation of organic shapes and geometric patterns.